The Need for Comprehensive Evaluation in Science Education. - Kumar, David D.; Altschuld, James W. (Review of Policy Research)
This article argues for policies regarding the implementation of evaluation as an integral part of science education reform. Approaches to evaluation should be made comprehensive enough to include multiple methods and, through their use, to gain in-depth information on large-scale science education programs and projects. There must be a sustained commitment from stakeholders such as the National Science Foundation to support the training of specialists in the evaluation of science education. Specialists who are able to arrive at independent conclusions that are meaningful and beneficial for science teaching and learning are needed. Evaluation recommendations posited by the authors should be put through careful analysis and feasibility testing before moving to widespread adoption. Reprinted by permission of the publisher.